2009
DOI: 10.1080/03602530802602880
|View full text |Cite
|
Sign up to set email alerts
|

Xenobiotic metabolizing enzymes and metabolism of anthelminthics in helminths

Abstract: Anthelminthics remain the only accessible means in the struggle against helminth parasites, which cause significant morbidity and mortality in man and farm animals. The treatment of helminthic infections has become problematic because of frequent drug resistance of helminth parasites. The development of drug resistance can be facilitated by the action of xenobiotic metabolizing enzymes (XMEs). In all organisms, XMEs serve as an efficient defense against the potential negative action of xenobiotics. The activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 166 publications
2
73
0
2
Order By: Relevance
“…The presence of reductive drug metabolism in M. expansa was proven by results from ex vivo cultivations, where the less potent FLU and MBZ metabolites with reduced carbonyl group were found (Dayan, 2003;Ceballos et al 2011). These metabolites were previously identified in other helminths species: Haemonchus contortus, Hymenolepis diminuta and Dicrocoelium dendriticum (Cvilink et al 2009a). From in vitro experiments it can be seen that the formation of reduced metabolites took place in cytosollike fraction of M. expansa.…”
Section: Discussionmentioning
confidence: 89%
“…The presence of reductive drug metabolism in M. expansa was proven by results from ex vivo cultivations, where the less potent FLU and MBZ metabolites with reduced carbonyl group were found (Dayan, 2003;Ceballos et al 2011). These metabolites were previously identified in other helminths species: Haemonchus contortus, Hymenolepis diminuta and Dicrocoelium dendriticum (Cvilink et al 2009a). From in vitro experiments it can be seen that the formation of reduced metabolites took place in cytosollike fraction of M. expansa.…”
Section: Discussionmentioning
confidence: 89%
“…Despite the fundamental and conserved role of xenobiotic detoxification in drug resistance, these processes are poorly understood in nematodes. The limited knowledge of these processes in helminths has been reviewed in detail recently (Cvilink et al 2009) and we only summarize it here briefly.…”
Section: Xenobiotic Detoxification Promotes Multidrug Resistancementioning
confidence: 99%
“…In animal cells, xenobiotic detoxification is modeled as occurring in three sequential and interdependent phases. In phase I, enzymes such as cytochrome P450s, short-chain dehydrogenases, and reductases uncover or insert reactive and hydrophilic groups onto xenobiotics leaving them more accessible for further processing (Iyanagi 2007; Cvilink et al 2009). The genome of Caenorhabditis elegans, the free-living genetic model nematode, is predicted to contain 86 cytochrome P450s and 68 short-chain dehydrogenases (Lindblom and Dodd 2006; the genome of Pristionchus pacificus , a beetle-associated nematode, is predicted to contain 198 cytochrome P450s (Dieterich et al 2008).…”
Section: Xenobiotic Detoxification Promotes Multidrug Resistancementioning
confidence: 99%
“…In sheep, it has been shown that this biotransformation is carried out by the flavin monooxygenase (FMO) and cytochrome P450 (CYP 450) enzyme systems (Virkel et al 2006). The metabolism transforms the drug into more polar metabolites that are excreted more easily (Cvilink et al 2009). F. hepatica has also been shown to have the ability to metabolise TCBZ (Mottier et al 2004;Robinson et al 2004).…”
Section: Introductionmentioning
confidence: 98%